Pathogenesis of Chronic Plaque Psoriasis and Its Intersection With Cardio-Metabolic Comorbidities - Gisondi, Paolo; Bellinato, Francesco; Girolomoni, Giampiero; Albanesi, Cristina (Frontiers in Pharmacology, 2020)
Psoriasis is a chronic, systemic immune-mediated disease characterized by development of erythematous, indurated, scaly, pruritic plaques on the skin. Psoriasis is frequently associated to comorbidities, including psoriatic arthritis, cardiovascular diseases, diabetes mellitus, obesity, non-alcoholic fatty liver disease and inflammatory bowel diseases. In this review, we discuss the pathophysiological relationship between psoriasis and cardio-metabolic comorbidities and the importance of therapeutic strategies to reduce systemic inflammation in patients with moderate-to-severe psoriasis. Pathogenesis of psoriasis and its comorbidities share both genetic predisposition and inflammatory pathways, which include the TNF and the IL-23/IL-17 pathways. These pathways are selectively addressed by biological treatments, which have substantially changed the outcomes of psoriasis therapy and affect positively comorbidities including reducing cardiovascular risk, allowing a more comprehensive approach to the patient.